Power balance analysis at the L-H transition in JET-ILW NBI-heated deuterium plasmas. (1st December 2022) - Vincenzi, P; Solano, E R; Delabie, E; Bourdelle, C; Snoep, G; Baciero, A; Birkenmeier, G; Carvalho, P; Cavedon, M; Chernyshova, M; Citrin, J; Fontdecaba, J M; et al.
Abstract: The understanding of the physics underlying the L-H transition has strong implications for ITER experimental reactor and demonstration power plant (DEMO). In many tokamaks, including JET, it has been observed that, at a particular plasma density, n e, min, the power necessary to access H-mode PL-H is minimum. In the present work, L-H transitions of JET deuterium plasmas heated by neutral beam injection (NBI) are studied for the first time by means of a power balance analysis to characterize the main contributions in the transition, through integrated transport modelling. In the pulses analysed, we do observe a minimum of the L-H power threshold in density, indicating the presence of density branches and of n e, min . Electron and ion heat fluxes at the transition are estimated separately. The electron/ion equipartition power results in favour of the ions, as shown by QuaLiKiz quasilinear gyrokinetic simulations, which predict a larger ion transport that causes T e > T i . The resulting edge ion heat flux also shows a clear change of slope below n e, min, similarly to ASDEX-Upgrade (AUG) NBI pulses (Ryter et al 2014 Nucl. Fusion 54 083003). JET NBI data are compared to radio-frequency heated AUG and Alcator C-mod pulses (Schmidtmayr et al 2018 Nucl. Fusion 58 056003), showing a different trend of the power, coupled to ions at the L-H transition with respect to the linearity observed in the radio-frequency heated plasmas. The presence of n e, min and the role of the ion heat flux is discussed in the paper, although it seems it is not possible to explain the presence of a PL-H minimum in density by a critical ion heat flux and by the equipartition power for the JET NBI-heated plasmas analysed.